[Rezension von: Popielska-Grzybowska, Joanna, Everything as one : a linguistic view of the Egyptian creator in the "Pyramid texts"] - Theis, Christoffer (JAOS, 2023)
Everything as One: A Linguistic View of the Egyptian Creator in the Pyramid Texts. By Joanna Popielska-Grzybowska. Travaux de l'Institut des Cultures Méditerranéennes et Orientales de l'Académie Polonaise des Sciences, vol. 5. Wiesbaden: Harrassowitz Verlag, 2020. Pp. 400. €71 (paper).